Determination of the properties and loading efficiency of encapsulated BSA-FITC and dexamethasone for drug delivery systems; IOP Conference Series: Materials Science and Engineering; Vol. 597 : Prospects of Fundamental Sciences Development (PFSD-2019) - Chudinova E. A. Ekaterina Aleksandrovna; Surmeneva M. A. Maria Alexandrovna; Koptyug A. V. Andrey Valentinovich; Sokolova V. Viktoriya; Primak O. Oleg; Bouckercha S.; Epple M. Matthias; Surmenev R. A. Roman Anatolievich (2019, 2019)
Title screen